2021
DOI: 10.1161/jaha.120.017405
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the Cardiac Autonomic Nervous System Activity in Children and Adolescents

Abstract: Background Despite the increasing interest in cardiac autonomic nervous activity, the normal development is not fully understood. The main aim was to determine the maturation of different cardiac sympathetic‐(SNS) and parasympathetic nervous system (PNS) activity parameters in healthy patients aged 0.5 to 20 years. A second aim was to determine potential sex differences. Methods and Results Five studies covering the 0.5‐ to 20‐year age range provided im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 67 publications
4
33
0
4
Order By: Relevance
“…Despite numerous assertions in the literature to the contrary, the absolute values of baseline RSA of children with ASD are almost all within the normal range. The wide range of normal RSA values in children was documented by Harteveld et al, who reported on 4,822 children aged 0.5–20 years ( 25 ). Harteveld et al ( 25 ) used the peak-valley method, measuring RSA by subtracting the shortest inter-beat interval during inhalation from the longest inter-beat interval during exhalation, and found that for 328 children aged 13–15, the RSA ranged from 18.7 to 186.7 ms (2.5–97.5 percentile), hence a very wide normal range.…”
Section: Critical Analysis Of Hrv Parameter Assessmentsmentioning
confidence: 88%
See 3 more Smart Citations
“…Despite numerous assertions in the literature to the contrary, the absolute values of baseline RSA of children with ASD are almost all within the normal range. The wide range of normal RSA values in children was documented by Harteveld et al, who reported on 4,822 children aged 0.5–20 years ( 25 ). Harteveld et al ( 25 ) used the peak-valley method, measuring RSA by subtracting the shortest inter-beat interval during inhalation from the longest inter-beat interval during exhalation, and found that for 328 children aged 13–15, the RSA ranged from 18.7 to 186.7 ms (2.5–97.5 percentile), hence a very wide normal range.…”
Section: Critical Analysis Of Hrv Parameter Assessmentsmentioning
confidence: 88%
“…The wide range of normal RSA values in children was documented by Harteveld et al, who reported on 4,822 children aged 0.5–20 years ( 25 ). Harteveld et al ( 25 ) used the peak-valley method, measuring RSA by subtracting the shortest inter-beat interval during inhalation from the longest inter-beat interval during exhalation, and found that for 328 children aged 13–15, the RSA ranged from 18.7 to 186.7 ms (2.5–97.5 percentile), hence a very wide normal range. In a personal communication, Harteveld calculated the range of RSA values (2.5–97.5 percentile) in 99 typically developing children, aged 4–18, to be 4.5–8.8 ln(ms 2 ) ( Table 1 ).…”
Section: Critical Analysis Of Hrv Parameter Assessmentsmentioning
confidence: 88%
See 2 more Smart Citations
“…These results suggest that the Poincaré plot may be superior to the frequency-domain indexes of HRV in comparing the autonomic nervous activities between children with VVS and POTS. Moreover, the autonomic functions in children gradually develop and mature with age ( 43 ). This study considered age as a factor and a stratified analysis was implemented to ensure that the results were accurate.…”
Section: Discussionmentioning
confidence: 99%